Pyoderma gangrenosum – retrospective study of 30 patients hospitalized in the Department of Dermatology, Venereology and Allergology, University of Medicine, Wroclaw in years 2000-2010 - Jankowska-Konsur, Alina; Maj, Joanna; Hryncewicz-Gwóźdź, Anita (Dermatology Review/Przegląd Dermatologiczny, 2012)
Introduction . Pyoderma gangrenosum (PG) is an uncommon, non-infectious, inflammatory disease of unknown aetiology, most frequently in the form of ulceration. In 50% of cases, PG is associated with systemic diseases. Objective. Retrospective analysis of patients with pyoderma gangrenosum hospitalized in the Department of Dermatology, Venereology and Allergology, University of Wrocław in years 2000-2010. Material and methods . We analysed the clinical and histopathological picture, clinical course and treatment of 30 patients. Results . The mean age of the studied group was 43.9 years and predominance of women (63.3%) was observed. There were 2 paediatric cases. In 46.7% of cases, concomitance of systemic diseases was disclosed, most frequently Crohn disease. The typical ulcerous form was present in 93.3% of cases. The most common sites of the lesions were shanks (66.7%), thighs and buttocks (30%). The lesions were numerous in 40% of patients, and in this group an association with internal disease was more frequent. The treatment of choice were systemic corticosteroids, commonly associated with cyclosporine. Conclusions . Pyoderma gangrenosum is a rare disorder, appearing most frequently in middle aged women, requiring thorough screening in the search for systemic diseases well responding to the treatment with systemic corticosteroids and cyclosporine.